(untitled) (Journal of Pathology of Nepal, 2018)
Filariasis is a chronic disabling parasitic disease causing a major public health problem in tropical areas of Southeast Asia. It is endemic in India, China, Nepal, Indonesia, parts of Asia and Africa. In Southeast Asia it is caused mainly by W. bancrofti and Brugia species. Microfilaria is known to be present in cytology smears prepared from swelling at various sites and also in different body fluids. However, upper arm swelling as a clinical presentation of filariasis is a very rare event. If cytology smears are screened with high index of suspicion in this group of otherwise asymptomatic patients, early institution of proper treatment can both prevent the complication of the disease as well as break the chain of transmission from healthy carriers.